Integration of Social-Emotional Skills (SSE) in Deep Learning for Grade IV-B Students: A Case Study at SD Negeri Rungkut Kidul II/581 Surabaya - Fery Nice Wulan Dari; Ganes Gunansyah; Julianto Julianto; Neni Mariana (Universitas Negeri Makassar, 2026)
This study aims to holistically describe the process of integrating social-emotional skills (SEL) into deep learning through project-based co-curricular activities among fourth-grade students of Class IV B at SDN Rungkut Kidul II/581 Surabaya. The main focus is directed toward three dimensions of SEL, namely collaboration, communication, and emotional regulation. This research employed a single instrumental case study design. The research subjects consisted of 28 students and three teachers (classroom teacher, religious education teacher, and physical education teacher). Data collection techniques included passive participant observation, semi-structured in-depth interviews, and document analysis. Data analysis encompassed data condensation, data display, as well as conclusion drawing and verification. The results indicate that the microgreens project served as an effective vehicle for integrating SEL, with the following key findings. First, collaboration skills evolved from unbalanced task distribution toward prosocial behavior and positive interdependence, characterized by students' willingness to help peers without being asked as well as collective responsibility for maintaining environmental cleanliness. Second, communication skills were marked by the internalization of communicative ethics through the habitual use of polite expressions such as